2015
DOI: 10.1097/mao.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

Reverberation Time Influences Musical Enjoyment With Cochlear Implants

Abstract: Minimization of RT60 may be a useful strategy for increasing musical enjoyment under CI conditions, both in altering existing music as well as in composition of new music.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Alternatively, the noise reduction algorithm may have increased the complexity of the signal through frequent short attenuations of musical notes. This increase in complexity is known to diminish music enjoyment (13,14). Furthermore, the dynamic, constantly varying way in which the noise reduction algorithm attenuates various frequency channels could potentially lead to disturbances that create a more negative music listening experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the noise reduction algorithm may have increased the complexity of the signal through frequent short attenuations of musical notes. This increase in complexity is known to diminish music enjoyment (13,14). Furthermore, the dynamic, constantly varying way in which the noise reduction algorithm attenuates various frequency channels could potentially lead to disturbances that create a more negative music listening experience.…”
Section: Discussionmentioning
confidence: 99%
“…A study in CI users with a MED-EL device on one side and a Cochlear Nucleus on the other found no significant difference in music enjoyment when either device type was used exclusively (12). Recently, we have shown that the novel strategy of re-engineering the original piece of music by either reducing the complexity of music by decreasing the number of musical instruments or minimizing reverberation can increase music enjoyment (13,14).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, reductions in reverberation time and instrumental complexity have been shown to enhance enjoyment under CI conditions. 11,12 Studies have also shown that CI users may enhance their listening experience by controlling their listening environment (with quiet rooms and quality sound equipment) and using visual cues (like watching performers). 23,24 Other considerations, including rhythmic complexity, musical tone duration, and instrument type may also have a role.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Certo et al demonstrated that minimization of reverberation time increased music enjoyment under CI conditions. 12 Consequently, approaches that decrease music complexity (e.g. music reengineering) may prove fruitful in enhancing music enjoyment.…”
Section: Introductionmentioning
confidence: 99%